POLICY, PRACTICE AND PERCEPTIONS OF QINGZHEN (HALAL) IN CHINA - Sai, Yukari (Online Journal of Research in Islamic Studies, 2014)
This article examines how Muslims and non-Muslims share halal values in everyday life by exploring top-down standardisation of halal and bottom-up daily food practices in non-Muslim society, specifically, case study among the Hui and Han people in the People’s Republic of China. As global awareness of the halal market has increased, local governments in China and around the world have introduced regulations to manage halal food production. This policy environment also facilitates the entry of various actors into business — and uses international connections and co-operation to ensure the reliability and authority of halal marks in China. Additionally, in terms of access to and the culinary image of halal food in everyday life, it was found that Muslims prioritise service providers’ honesty and responsibility, while non-Muslims consume halal food as an alternative to local cuisine or as an economic tool.